Application of Artificial Intelligence in the Development of Automated Website Creation to Support Digital Transformation - Fajar Firmansyah; Syafari Suryo Pranoto; Luthfy Hanifan Bil Haq; Ilham Wibawa Kusumah Dinata (Universitas Panca Marga, 2026)
The rapid advancement of digital technology has encouraged organizations and educational institutions to adopt digital transformation strategies to improve efficiency and service quality. Website development plays a crucial role in supporting this transformation; however, traditional website creation often requires significant time, technical expertise, and continuous maintenance. This study aims to investigate the application of Artificial Intelligence (AI) in automated website development to support digital transformation. The proposed system utilizes Artificial Intelligence and Natural Language Processing (NLP) techniques to automatically generate website content, structure, and layout based on user requirements. A comparative analysis was conducted between conventional website development methods and AI-based automated website generation. The system performance was evaluated using five criteria: website development time, content update efficiency, information accuracy, user satisfaction, and website adaptability. Development time was measured in minutes required to complete a website, content update efficiency by the average time required to publish updates, information accuracy through expert validation, user satisfaction using a 5-point Likert-scale questionnaire based on the System Usability Scale (SUS), and website adaptability by assessing the system's ability to accommodate changing user requirements. Statistical analysis was performed using descriptive statistics and paired sample t-tests (p < 0.05) to determine significant differences between the conventional and AI-based approaches. The results indicate that AI implementation significantly improves website development speed, content update efficiency, information accuracy, user satisfaction, and website adaptability. Furthermore, the automation process reduces administrative workload and enables real-time content updates. The findings demonstrate that AI-based website development provides a more efficient, scalable, and adaptive solution for organizations seeking to accelerate digital transformation. Therefore, the integration of Artificial Intelligence into website development can enhance operational effectiveness and improve digital service delivery.